Advanced Testing and Characterization of Bituminous Materials, Two Volume Set - Loizos, Andreas; Partl, Manfred N.; Scarpas, Tom; Al-Qadi, Imad L. (Taylor & Francis, 2009)
Bituminous materials are used to build durable roads that sustain diverse environmental conditions. However, due to their complexity and a global shortage of these materials, their design and technical development present several challenges. Advanced Testing and Characterisation of Bituminous Materials focuses on fundamental and performance testing